PENGARUH PENAMBAHAN ABU CANGKANG PENSI TERHADAP KUAT GESER TANAH LEMPUNG - Misbah, Misbah; Martha, Fiky (Ensiklopedia of Journal, 2022)
Land is a place that is usually used to build a foundation or building that supports all the loads of the structure or construction that stands on it, both building construction and road construction. If it is used for roads, it is important to check the soil so that the road construction that is built can last a long time. In some areas, the soil needs to be researched because the soil conditions in the area contain a lot of clay so it is necessary to check the shear strength of the soil. To increase the shear strength of the soil, it is necessary to conduct research using several methods, including using pensi shell ash as an additional material. The pencil material used is passed filter no. 200, with the percentage of pensi shell ash in the soil content of 0%, 6%, 8% and 10%. The tests carried out consisted of testing the physical properties and mechanical properties of the soil. Testing of the physical properties of the soil includes the sieve no. 200 test, the specific gravity (gs) test, the Atterberg limit test. Meanwhile, testing of mechanical properties includes soil density, optimum moisture content, cohesion and internal shear angle. The results showed that the addition of pensi shell ash to the original soil with a treatment period of 3 days, the addition of 6% pensi shell ash had a cohesion value (c) of 13.12 kN/m² and a shear angle of 5.46⁰, and for the addition of 8% pensi shell ash, the cohesion value (c) is 27.05 kN/m² and the shear angle is 1.66⁰ and for the addition of 10% pensi shell ash, the cohesion value (c) is 12.5 kN/m² and the shear angle is 8.66⁰. The highest value for shear strength was obtained at the addition of 10% pensi shell ash. Keywords: Clay, Pensi shell ash, inner shear angle.